|
|
Line 1: |
Line 1: |
| ====Working results 1==== | | ====Working results 1==== |
| :<math> | | :<math> |
− | \mathbf{q} = \frac{2 \pi}{\lambda} \begin{bmatrix} \sin \theta_f \cos \alpha_f \\ \cos \theta_f \cos \alpha_f - 1 \\ \sin \alpha_f \end{bmatrix} | + | \begin{alignat}{2} |
| + | \mathbf{q} & = \frac{2 \pi}{\lambda} \begin{bmatrix} \sin \theta_f \cos \alpha_f \\ \cos \theta_f \cos \alpha_f - 1 \\ \sin \alpha_f \end{bmatrix} \\ |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} \sin \left( \arctan\left[ \frac{x}{d} \right] \right) \cos \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) \\ \cos \left( \arctan\left[ \frac{x}{d} \right] \right) \cos \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) - 1 \\ \sin \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) \end{bmatrix} \\ |
| + | |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x/d}{\sqrt{1+\left(x/d \right)^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} \\ |
| + | \frac{1}{\sqrt{1+\left(x/d \right)^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} - 1 \\ |
| + | \frac{z \cos \theta_f}{\sqrt{d^2+z^2 \cos^2 \theta_f }} \end{bmatrix} \\ |
| + | |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x d}{\sqrt{d^2+x^2 }} \frac{1}{\sqrt{d^2+z^2\cos^2 \theta_f}} \\ |
| + | \frac{d}{\sqrt{d^2+x^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} - 1 \\ |
| + | \frac{z \cos \theta_f}{\sqrt{d^2+z^2 \cos^2 \theta_f }} \end{bmatrix} \\ |
| + | |
| + | |
| + | \end{alignat} |
| </math> | | </math> |
| + | |
| + | |
| + | \frac{1}{\sqrt{1+\left(u\right)^2}} \\ |
| + | \frac{u}{\sqrt{1+\left(u\right)^2}} \\ |
| | | |
| ====Working results 2 (contains errors)==== | | ====Working results 2 (contains errors)==== |
Revision as of 11:56, 13 January 2016
Working results 1
![{\displaystyle {\begin{alignedat}{2}\mathbf {q} &={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \theta _{f}\cos \alpha _{f}\\\cos \theta _{f}\cos \alpha _{f}-1\\\sin \alpha _{f}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\\\cos \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)-1\\\sin \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {x/d}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {1}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {xd}{\sqrt {d^{2}+x^{2}}}}{\frac {1}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {d}{\sqrt {d^{2}+x^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/6ea671cecdf06e0446180db0c1e73d2bb4fd81a5)
\frac{1}{\sqrt{1+\left(u\right)^2}} \\
\frac{u}{\sqrt{1+\left(u\right)^2}} \\
Working results 2 (contains errors)
As a check of these results, consider:

Where we used:
![{\displaystyle {\begin{alignedat}{2}\sin(\arctan[u])&={\frac {u}{\sqrt {1+u^{2}}}}\\\sin \theta _{f}&=\sin(\arctan[x/d])\\&={\frac {x/d}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {x}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/fc9628f0d308053600f4e02d8f80c69fc9f356d0)
And, we further note that:
![{\displaystyle {\begin{alignedat}{2}\cos(\arctan[u])&={\frac {1}{\sqrt {1+u^{2}}}}\\\cos \theta _{f}&={\frac {1}{\sqrt {1+(x/d)^{2}}}}\\&={\frac {d^{2}}{\sqrt {d^{2}+x^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/584da470743b7feac2b55988526dabce5b4313c4)
Continuing:
